Propane Dehydrogenation in a Modified Porous Membrane Reactor for Producing Propylene with Chemical and Polymer Grades - Azis Trianto; Yazid Bindar; Noezran Noezran (ASEAN Journal of Chemical Engineering, 2005)
Propane dehydrogenation is a promising route for producing propylene to replace traditional cracking methods. A membrane reactor offers a possibility to produce not only chemical grade but also polymer grade of propylene. The purpose of the present study is to evaluate the performance of a Modified Porous Membrane Reactor (MPMR) in producing these two propylene grades simultaneously. The study involves evaluations based on thermodynamics and process flow sheeting. The performance of this reactor is compared to that of conventional reactor. At first, the thermodynamics is conducted using minimum Gibb's Energy approach. Then the process flow sheeting evaluation is built using the HYSYS simulator. The effect of inert gas (steam) concentration in both sweep and feed sides is investigated. The thermodynamics study results optimum temperature and inert gas concentration to obtain these two grades of propylene simultaneously. The propylene with polymer grade above 99% is produced from the sweep side outlet. The propylene with chemical grade is produced from the feed side outlet. The simultaneous production of these two grades of propylene has benefit in vanishing propane-propylene splitter. Keywords: Membrane reactor, porous membrane, propane dehydrogenation, propylene production, and process simulation.